Characteristics of the paravertebral muscle in adult degenerative scoliosis with PI-LL match or mismatch and risk factors for PI-LL mismatch - Guo, Jichao; Xie, Dongxiao; Zhang, Jinniu; Ding, Wenyuan; Zhao, Boyang; Li, Zhaohui; Huo, Yachong (Frontiers in Surgery, 2023)
Objective Pelvic incidence (PI) minus the lumbar lordosis (LL) angle (PI-LL) correlates with function and disability. It is associated with paravertebral muscle (PVM) degeneration and is a valuable tool for surgical planning of adult degenerative scoliosis (ADS). This study aims to explore the characteristics of PVM in ADS with PI-LL match or mismatch and to identify the risk factors for PI-LL mismatch. Methods A total of 67 patients with ADS were divided into PI-LL match and mismatch groups. The visual analog scale (VAS), symptom duration, and Oswestry disability index (ODI) were used to assess patients’ clinical symptoms and quality of life. The percentage of fat infiltration area (FIA%) of the multifidus muscle at the L1-S1 disc level was measured by using MRI with Image-J software. Sagittal vertical axis, LL, pelvic tilt (PT), PI, sacral slope, and the asymmetric and average degeneration degree of the multifidus were recorded. Logistic regression analysis was done to identify the risk factors for PI-LL mismatch. Results In the PI-LL match and mismatch groups, the average FIA% of the multifidus on the convex side was less than that on the concave side (P < 0.05). There was no statistical difference of asymmetric degeneration degree of the multifidus between the two groups (P > 0.05). In the PI-LL mismatch group, the average degeneration degree of the multifidus, VAS, symptom duration, and ODI were significantly higher than that in the PI-LL match group, respectively (32.22 ± 6.98 vs. 26.28 ± 6.23 (%), 4.33 ± 1.60 vs. 3.52 ± 1.46, 10.81 ± 4.83 vs. 6.58 ± 4.23 (month), 21.06 ± 12.58 vs. 12.97 ± 6.49, P < 0.05). The average degeneration degree of the multifidus muscle was positively correlated with the VAS, symptom duration, and ODI, respectively (r = 0.515, 0.614, and 0.548, P < 0.05). Sagittal plane balance, LL, PT, and the average degeneration degree of the multifidus were the risk factors for PI-LL mismatch (OR: 15.447, 95% CI: 1.274–187.269; OR: 0.001, 95% CI: 0.000–0.099; OR: 107.540, 95% CI: 5.195–2,225.975; OR: 52.531, 95% CI: 1.797–1,535.551, P < 0.05). Conclusion The PVM on the concave side was larger than that on the convex side in ADS irrespective of whether PI-LL matched or not. PI-LL mismatch could aggravate this abnormal change, which is an important cause of pain and disability in ADS. Sagittal plane imbalance, decreased LL, higher PT, and larger average degeneration degree of the multifidus were independent risk factors for PI-LL mismatch.